2021
DOI: 10.1177/21677026211043862
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy and Moral-Dilemma Judgment: An Analysis Using the Four-Factor Model of Psychopathy and the CNI Model of Moral Decision-Making

Abstract: A major question in clinical and moral psychology concerns the nature of the commonly presumed association between psychopathy and moral judgment. In the current preregistered study ( N = 443), we aimed to address this question by examining the relation between psychopathy and responses to moral dilemmas pitting consequences for the greater good against adherence to moral norms. To provide more nuanced insights, we measured four distinct facets of psychopathy and used the CNI model to quantify sensitivity to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…This finding supports the view that some psychopathic traits are related to an indifference to moral guidelines that is separable from eventual endorsement of such behavior (see cf. Cima et al., 2010 ; Luke et al., 2021 ). In line with this, earlier research has linked utilitarian choices with impaired social cognition rather than with deliberative reasoning (Duke & Bègue, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding supports the view that some psychopathic traits are related to an indifference to moral guidelines that is separable from eventual endorsement of such behavior (see cf. Cima et al., 2010 ; Luke et al., 2021 ). In line with this, earlier research has linked utilitarian choices with impaired social cognition rather than with deliberative reasoning (Duke & Bègue, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this complicates the exact comparability among dilemmas. Future research using moral dilemmas in experimental set‐ups that include different conditions should take this issue into account and consider randomizing the dilemmas among conditions (Luke et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the relationship between secondary psychopathy and utilitarian response tendencies is contrary to the hypotheses of the present study, it is consistent with previous studies. Luke et al (2022) found a marginally significant positive correlation between lifestyle–antisocial traits (similar to secondary psychopathy) and sensitivity to consequences (similar to utilitarian response tendencies), suggesting that people with lifestyle–antisocial traits are more likely to maximize outcomes in moral dilemmas [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given these limitations in criminal procedure, it is not easy to gain knowledge about the offender’s self-determination (Ferrua, 2020), free will and moral judgment (Gulotta, 2018). The literature includes studies primarily concerned with juvenile offenders (Ashkar and Kenny, 2007) and their moral development (Colby and Kohlberg, 1987) or studies of low empathy and offending (Jolliffe and Farrington, 2007) or impaired moral judgment due to mental disorders (de Vel-Palumbo et al , 2021) or psychopathy (Cacace et al , 2022; Luke et al , 2021). Other studies have focused on how offenders and their antisocial behavior are morally perceived by the general population (Herzog and Einat, 2016).…”
Section: Introductionmentioning
confidence: 99%